Merancang Sistem Kontrol Pintu Air Berbasis Arduino dengan Fitur Self-Check Sensor - Balqis Yafis; Rahmat ; (Jurnal Tika, 2021)
The use of Arduino-Based floodgates aims to address the issue of flooding. The goal of this research was to create a system that could monitor water levels and control floodgatesUltrasonic sensor was used to measure water level, as the water level becomes the indicator to open and close the floodgates. The ultrasonic sensor is mounted on the dam and measures the distance between the water’s surface and the sensor transmitter. The results of the measurement of the water level are used to control the floodgates. Sensor measurement results are not always valid, given the age of the sensor and the terrain around the dam is quite challenging. The self-check sensor feature is introduced in this study as a way to overcome detection faults in the system, where ultrasonic sensors can perform self-monitoring by relying solely on their neighbours. In general, the process is carried out in four stages, starting from the stage of reading the sensor, the stage transmitting and receiving data from the Arduino, the stage of detecting sensor’s value, the stage of displaying the sensor values. At the stage of displaying the sensor value, there are four water level conditions, normal, waspada, siaga and bahaya. According to the test results, incorporating self-check sensors into the system enables for more efficient Arduino-based sluice control systems, as well as the possibility of detecting malfunctions caused by sensor damage